Application Of Fa-Ggbs Geopolymer As An Alternative Adsorbent For Heavy Metals Removal - Rabie, Mohamed Samir Mohamed Kamel (Universiti Sains Malaysia, 2021)
Since the beginning of time, humans have relied on surface water as a source of water. However, as more and more surface water are polluted by waste from human activities, this water supply is becoming less available. Elevated heavy metals concentrations in the surface water are one of the common issues. Adsorption has been proved to be the best process of water treatment because of its significant advantages. The adsorption assessment of GGBS shows good efficiency in copper removal as studied. GGBS is a by-product of the steel industry that has good structural and durable properties with fewer environmental effects. Therefore, this study aims to 1) To characterize the adsorbent based on the chemical composition using XRD, XRF, and leaching tests.; 2) determine the effectiveness of GGBS as an adsorbent in the removal of copper; 3) To compute adsorption isotherm analysis with Langmuir model and Freundlich model. Results showed very high efficiency of copper removal almost 100% with 2.5 g of adsorbent, 150 rpm as an agitation rate, and 3 hours as contact time. XRD study for GGBS showed high results for quartz (SiO2), calcite (CaCO3), and anorthite (CaAl2Si2O8). While XRF study showed high results for elements Si, Ca, and O with 30.35%, 24.33%, and 18.261%, respectively. Based on the experimental data, the adsorption phenomena in this study follow the Freundlich Isotherm model which assumes that their adsorption occurred in multilayer order onto the heterogenous surface of the adsorbent. The Freundlich adsorption also expressing that there is possibility lateral interaction between adsorbates.